Global Perspectives on US Foreign Policy From the Outside In - Burt, S.; Burt, S.; Añorve, D.; Añorve, D. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
This book explores aspects of US foreign policy, including the development process as well as the policy itself in respect to various countries and regions and some significant issues around the globe today. Providing insight into non-US perspectives of American foreign policy, the book contextualizes the effects of policy on external nations.